In situ synthesized electroactive and large dielectric BaF2/PVDF nanocomposite film for superior and highly durable self-charged hybrid photo-power cell. (1st September 2018) - Khatun, Farha; Thakur, Pradip; Amin Hoque, Nur; Kool, Arpan; Roy, Swagata; Biswas, Prosenjit; Bagchi, Biswajoy; Das, Sukhen
Graphical abstract: Highlights: Synthesis of BaF2 nanoparticles (NPs) incorporated PVDF thin films via in situ process followed by solution casting method. Achievement of 96% electroactive β phase nucleation in PVDF due to catalytic effect of BaF2 NPs. Development of giant dielectric BaF2 /PVDF thin film based Photo-power cell. The power cell exhibits a remarkable energy storage efficiency ∼79% with superior power density ∼18.7 W/m 2 . The power pack is able to glowing several LEDs with same intensity for long time span (∼7 days). Abstract: In present work, a simplistic, efficient and highly durable electroactive and high dielectric BaF2 nanoparticles (NPs) incorporated polyvinylidene fluoride (PVDF) thin film based Self-Charged Hybrid Photo-Power Cell (HPPC) has been designed which is able to self-charge under visible light illumination. The incorporation of NPs into the PVDF matrix has effectively enhanced the polar β crystallite nucleation (∼96%) and the dielectric value (∼2570) of the PVDF thin film. A composite dye film of TiO2 NPs, phenosafranine-polyvinyl pyrrolidone in the presence of H3 PO4 is acted as the light absorbing and photoelectrons generating part in the HPPC. The photo-electrons are stored in the energy storage part made of the in situ synthesized BaF2 NPs embedded PVDF thin film. Our HPPC is able to generate a photovoltage ∼1.3 V within 65 s under exposure of visible light (∼110 mW/cm 2 ) with superior energy storage efficiency ∼79%. The device has the ability of storing charge ∼1200 F/m 2 with power density ∼18.7 W/m 2 and charge density ∼1500 C/m 2 . Our light weighted self-charged power bank may be utilized as power supplier in portable electronic appliances.